Does higher education system moderate energy consumption and climate change nexus? Evidence from a small island - Katircioglu, Setareh; Katircioglu, Salih; Saqib, Najia (Springer, 2020)
This study estimates the effects of higher education development on climate changes through energy consumption in the case of Cyprus (North), which progressed successfully in this sector although countries other than Turkey do not recognize its state (Turkish Republic of Northern Cyprus). The results of this study reveal that there is strong evidence for the positive and significant impact of higher education growth on climate change via energy consumption. Therefore, it is concluded that educational development in Cyprus is a long-term contributor to the energy sector and, therefore, climate change.
Keywords: Higher education; Energy demand; Climate change; Cyprus